Up-regulated pathways in response to deformed wing virus infection in Apis mellifera (Hymenoptera: Apidae) - Quintana, Silvina (2019)
Transmission of viruses by Varroa destructor(Anderson &Trueman, 2000) to bees has been identified as one of the main threats to Apis mellifera L. colonies. It has also been suggested that synergistic parasite-pathogen interaction mediated by A. mellifera immunity can drive the collapse of honey bee colonies. We analyzed the relationship between deformed wing virus (DWV) viral load and gene expression levels of Toll Wheeler, cactus, domeless, TEPA, nitric oxide synthase, hymenoptaecin, vitellogenin, defensin, abaecinin winter bee samples ofA. mellifera with and without deformed wings. Samples were collected from hives in the field with high V. destructor infestation. In bees with deformed wings we found an increase in DWV titre and upregulation of genes in the Jak-STAT signalling pathway.